SOME RESULTS ABOUT CORETRACTABLE MODULES - Mohammed Ali Hadi, Inaam; Neamah Al-aeashi, Shukur (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
Throughout this paper, all rings have identities and all modules are unitary right modules. Let R be a ring and M an R-module. A module M is called coretractable if for each proper submodule N of M, there exists a nonzero homomorphism f from M/N into M. Our concern in this paper is to develop basic properties of coretractable modules and to look for any relations between coretractable modules and other classes of modules.